2005
DOI: 10.1007/bf03181498
|View full text |Cite
|
Sign up to set email alerts
|

Flow field around growing and rising vapour bubble by PIV measurement

Abstract: A study on flow field measurement around growing and rising vapour bubbles by use of PIV technique is presented. Bubbles were generated from single artificial cavities. Experiments have been conducted with saturated boiling of distilled water at atmospheric pressure. In the experiment fluid velocity field surrounding the bubbles was visualized by use of polyamide tracer particles and a sheet of a YAG pulse laser beam. The images were recorded with a cross-correlation CCD-camera. It has been shown that for lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
4
1
1
Order By: Relevance
“…Probably the most relevant source is Han and Griffith [34] who in some "rough" experiments determined the hydrodynamic disturbance caused by liing a spherical particle from a horizontal surface and found that it has a range of twice the size of the particle. A similar size has been claimed by Cieslinski et al [35] from PI� measurement of the �ow �eld around departing bubbles, although the quality of the images presented is rather poor. Since = 1 corresponds to the case where the whole surface is under the in�uence of bubbles, as calculated by (10) has to be limited to values smaller than this limit.…”
Section: Modeling Of Boiling At a Heated Wallsupporting
confidence: 86%
“…Probably the most relevant source is Han and Griffith [34] who in some "rough" experiments determined the hydrodynamic disturbance caused by liing a spherical particle from a horizontal surface and found that it has a range of twice the size of the particle. A similar size has been claimed by Cieslinski et al [35] from PI� measurement of the �ow �eld around departing bubbles, although the quality of the images presented is rather poor. Since = 1 corresponds to the case where the whole surface is under the in�uence of bubbles, as calculated by (10) has to be limited to values smaller than this limit.…”
Section: Modeling Of Boiling At a Heated Wallsupporting
confidence: 86%
“…Probably the most relevant source is Han and Griffith (1965) who in some "rough" experiments determined the hydrodynamic disturbance caused by lifting a spherical particle from a horizontal surface and found that it has a range of twice the size of the particle. A similar size has been claimed by Cieslinski (2005) from PIV measurement of the flow field around departing bubbles, although the quality of the images presented is rather poor.…”
Section: Other Influence Factors Bubble Influence Area/factorsupporting
confidence: 82%
“…The vortex ring generated inside the skirt is similar to a vortex ring behind a rising vapour bubble observed by Cieslinski et al (2005). The ratio of increment of the circulation to that of the initial one is 1.06 by using the values of 4.9 mm (0.11R), the diameter of the vortex core, and 12.3 mm (0.27R), the diameter of the vortex ring, in this experiment.…”
Section: Suctionsupporting
confidence: 72%